Beyond the dark web: navigating the risks of cannabis supply over the surface web. (4th July 2022) - Childs, Andrew; Bull, Melissa; Coomber, Ross
Abstract: Common depictions of buying and selling illicit drugs online centre on how drug market actors engage in dark web drug cryptomarkets, but the supply of illicit drugs also takes place in 'plain site' on the surface web. Drawing on netnographic observations and qualitative interviews with hard-to-reach buyers and vendors ( n = 20), this paper explores LeafedOut, a specific, popular surface web platform, that provides a conduit for local cannabis exchanges. We found that the platform enabled easy access and supply at the local level but increased some specific risks to those involved. Actors neutralised the perceived risks of drug supply over this surface web platform through the broader societal normalisation of cannabis use/supply, adopting encrypted messaging applications to cover 'digital traces', and developing various methods to establish trust with an exchange partner (e.g. review systems, sending selfies with drug paraphernalia, selectively choosing meet-up locations). This paper expands our understanding of the growing number of online illicit drug markets by shifting attention from dark web cryptomarkets to the much more widely accessed surface/clear web. Theoretical implications for the study of trust and risk in online illicit drug market exchanges are also considered.